A single-centre investigator-blinded randomised parallel group clinical trial to investigate the effect of probiotic strains Streptococcus salivarius M18 and Lactobacillus acidophilus on gingival health of paediatric patients undergoing treatment with fixed orthodontic appliances: study protocol. Issue 9 (8th September 2019) - Kaklamanos, Eleftherios G; Nassar, Rania; Kalfas, Sotirios; Al Halabi, Manal; Kowash, Mawlood; Hannawi, Haifa; Hussein, Iyad; Salami, Anas; Hassan, Ammar; Senok, Abiola C
Abstract : Background: There is limited data on the beneficial effects of probiotics on the gingival health of patients undergoing treatment with fixed orthodontic appliances. This study aims to compare the effect of probiotic tablets combined with regular oral hygiene versus regular oral hygiene alone on gingival status in these patients. The effect of probiotic intake on plaque formation and salivary microbiome composition will be also assessed. Methods and analysis: This is a 3 month single-centre, single blind (clinical and laboratory examiners), parallel group randomised controlled two arm superiority trial. Fifty paediatric patients attending the Postgraduate Orthodontic Clinic at the Hamdan Bin Mohammed College of Dental Medicine (HBMCDM), Mohammed Bin Rashid University of Medicine and Health Sciences (MBRU), Dubai, United Arab Emirates, who meet the eligibility criteria will be recruited. Block randomisation with 1:1 allocation and concealment of allocation will be carried out. The treatment group will receive probiotic tablets containing Streptococcus salivarius M18 and Lactobacillus acidophilus together with regular oral hygiene versus the control group on regular oral hygiene alone. Clinical examination and collection of saliva for microbiome assay will be carried out at baseline and end of study. Self-reporting by patients will be used to document acceptability and adverse effects. Statistically significant decrease in gingival bleeding on probing in the treatment group will be classified as primary outcome of treatment success. Statistically significant reduction in Plaque Index, Gingival Index and shift in the composition of the oral microbiome in favour of beneficial bacteria are secondary outcomes indicative of efficacy of probiotic intake. Ethics and dissemination: Ethical approval for the study has been granted by the HBMCDM, MBRU, Institutional Review Board (Reference #: MBRU-IRB-2018–015). Study findings will be disseminated via publication in peer-reviewed journal. Trial registration number: ISRCTN95085398